The Effect Of Debt To Equity Ratio, Sales Growth On Profitability With Good Corporate Governance As A Moderating Variable In The Manufacturing Sector Listed On The Indonesian Stock Exchange - Ega Dwi Lestari; Helma Malini; Wendy Wendy (UNIVED Press, 2025)
This study aims to examine the effect of Sales Growth and Liquidity on Profitability with Good Corporate Governance as a moderating variable. This form of research is Causal Associative research. The data collection technique in this research is a documentary study. The population in this study were manufacturing sector companies listed on the Indonesia Stock Exchange in the 2019-2023 period as many as 172 companies. Sampling in this study is using purposive sampling technique. The method of analysis in this study with ordinary Least Square (OLS) panel data regression EViews 12. The results of panel data regression analysis and Moderated Regrassion Analysis (MRA) in this study show that the moderating variable Good Corporate Governance (GCG) has an effect on Debt to Equity Ratio, Sales Growth (SG) has a positive effect on profitability. has no significant effect on profitability. Moderated Regression Test Analysis of DER variables can moderate Good Corporate Governance (GCG) has a positive and significant effect on sales growth. Good Corporate Governance cannot moderate liquidity (CR) has a positive and significant effect on profitability.